2017
DOI: 10.1038/srep43397
|View full text |Cite
|
Sign up to set email alerts
|

bHLH142 regulates various metabolic pathway-related genes to affect pollen development and anther dehiscence in rice

Abstract: Apposite development of anther and its dehiscence are important for the reproductive success of the flowering plants. Recently, bHLH142, a bHLH transcription factor encoding gene of rice has been found to show anther-specific expression and mutant analyses suggest its functions in regulating tapetum differentiation and degeneration during anther development. However, our study on protein level expression and gain-of-function phenotype revealed novel aspects of its regulation and function during anther developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…Severe glume developmental defects can lead to infertility in rice (Xiao et al, 2009;Hong et al, 2010). Similarly, pollination failure due to anther indehiscence leads directly to sterility (Thangasamy et al, 2011;Zhou et al, 2011;Ranjan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Severe glume developmental defects can lead to infertility in rice (Xiao et al, 2009;Hong et al, 2010). Similarly, pollination failure due to anther indehiscence leads directly to sterility (Thangasamy et al, 2011;Zhou et al, 2011;Ranjan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We found significant upregulation of UDT1 , GAMYB , TDR , and EAT1 at the early stage in OE142 anthers. In contrast, no alternation in expression of these master regulators was detected in the RNA-seq data presented by Ranjan et al (2017). Another potential shortfall of their study is the pollen development stages used for transcriptomic profiling.…”
Section: Discussionmentioning
confidence: 87%
“…For example, the known pollen wall synthesis marker genes such as OsC4 , LTP45 , CYP703A3 , and C6 were upregulated but CYP704B2 was downregulated in their OE line (Ranjan et al, 2017, their Table 1). This is contradictory, as it has been clearly shown that in the pollen development regulatory network bHLH142 is located upstream of Cyp703A3 , Cyp704B2 , MS2 , and C6 and they are involved in the same sporopollenin biosynthesis pathway (Aya et al, 2011; Ko et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…() and Ranjan et al . (). Tissue blocks of the appropriate size and orientation were sectioned using a rotary microtome (Leica Biosystems, USA) to obtain strips of 8‐ to 10‐μm‐thick sections, which were flattened by floating for 1–2 min at 50–55°C.…”
Section: Methodsmentioning
confidence: 97%
“…() and Ranjan et al . (). The dehydrated samples were further processed by critical‐point drying and examined by SEM (Evo LS25; Zeiss).…”
Section: Methodsmentioning
confidence: 97%